Radical radiation therapy for esophageal carcinoma in situs inversus totalis with the history of surgery for lung cancer: a case report - Chen, Yi; Xu, Xinmin; Xu, Xia; Li, Ming; Ma, Qunfeng; Ding, Shubo (Frontiers in Oncology, 2025)
Situs inversus totalis (SIT) is a rare congenital anatomical variation. This case report describes the first instance of a patient with both lung and esophageal cancer along with SIT. Additionally, it presents the first successful radical radiation therapy for esophageal carcinoma with SIT. The patient underwent a left upper lobectomy with lymph node dissection using video-assisted thoracic surgery (VATS) for lung cancer in 2021 and radical radiotherapy for esophageal cancer in 2023.